Geotechnical Analysis of Mining Based on Topography and Geomorphology for Estimation of Limestone Resources and Reserves - Rukayah Rukayah (Journal La Multiapp, 2026)
Reef limestone is an industrial mineral with high economic value that is widely utilized in construction and cement industries. North Moyo District, Sumbawa Regency, contains tectonically uplifted limestone deposits, yet quantitative assessments of rock mass continuity and resource–reserve estimation remain limited. This study aims to identify geological characteristics, lithology, and fracture structures, and to estimate limestone resources and reserves using digital three-dimensional modeling. The research was conducted using a descriptive, geotechnical, and quantitative approach through the collection of primary data, including outcrop observations, elevation measurements, and fracture mapping, as well as secondary data such as regional geological maps, geomorphological information, and satellite imagery. Surface elevation data were processed using three-dimensional modeling to generate existing and design pit surfaces, and volumetric analysis was performed using the cut and fill method. Resource classification was divided into inferred, indicated, and measured categories, while reserve estimation applied a loss factor correction. The results show that the reef limestone exhibits a massive structure, porous texture, and fossil fragments with an effective thickness exceeding five meters. Fracture patterns are dominated by northwest–southeast and northeast–southwest orientations, consistent with regional tectonics. The estimated measured resource volume is 234,977 cubic meters, while proven reserves reach 226,643 cubic meters after correction. The limestone demonstrates strong lateral and vertical continuity, indicating a stable and homogeneous rock mass suitable for quarry mining. Three-dimensional modeling effectively represents field conditions and confirms the potential of reef limestone as a sustainable industrial material in North Moyo District.